Menganalisis Perilaku Kepemimpinan Kepala Sekolah Dalam Meningkatkan Kinerja Guru Di Madrasah Ibtidaiyah Negeri (MIN) 15 Bintaro - Hasyim Asy’ari; Syabilla Putri Atmawijaya; Ahmad Sulthan Nagip; Aesha Najwa Alia (Universitas Katolik Widya Karya Malang, 2023)
Effective leadership from a school principal is the key to improving the quality and performance of teachers as learning agents in madrasas. This study aims to find out and analyze in depth the leadership behavior of school principals in improving teacher performance at public elementary schools (MIN) 15 Bintaro. This study uses a descriptive qualitative research method. The research subject is the head of the school. Sources of data obtained through observation, interviews and taken from various literature relevant to the research material. The results of the study show that: (1) The principal's leadership behavior in improving teacher performance at MIN 15 Binatro, namely: the principal has influenced and mobilized subordinates, the principal determines the tasks of the teachers and provides training so that teacher performance increases, the principal is able to communicate effectively with teachers, principals involve all interested parties in making decisions; (2) Policies that can be implemented by school principals to improve teacher performance, namely: establishing cooperative relationships with teachers, measuring teacher performance by looking at the abilities of their students, and paying attention to the methods teachers use to teach; (3) In improving teacher performance the principal of the MIN 15 Bintaro school seeks to improve the discipline and responsibility of teachers.